PENGATURAN POLA MAKAN TERHADAP KEBERHASILAN TERAPI PCOS - Adenias Lutfia Ningrum (Yayasan Pendidikan Medika Indonesia, 2021)
PCOS infertility is caused by anovulation, wherein the follicle develops only 10 mm in size and PCOS develops when the ovaries are stimulated to produce excess amounts of androgen hormones. Diet and regular exercise can reduce body weight and have an effect on hormone levels in the circulation. The purpose of the article is to determine dietary regulation on the success of PCOS therapy. The article was compiled by searching the literature sources through Garuda and Sinta's database from 2000-2019 with a total of 14 articles. The keywords used in the search were PCOS, non-pharmacological therapy, and diet. The method used for analysis is systematic literature review which identifies, assesses, and then interprets all findings in a study to answer a research question by summarizing the results of the study. The results of the search for articles found that dietary regulation can increase the success of PCOS therapy. Types of food that can improve the function of the reproductive system are foods that contain lots of folic acid, iron, vitamin C, vitamin E, vitamin B6, zinc, aluminum, and calcium. Weight loss can affect the menstrual cycle because a decrease in body fat percentage will occur along with weight loss so that it can reduce the risk of menstrual cycle disorders, improve the ovulation process, and improve fertility levels.